Dysregulation of Autonomic Cardiac Control by Traumatic Stress and Anxiety - J. P. Ginsberg (Frontiers Research Topics, 2016)
Current understanding of the interplay between sympathetic and parasympathetic influences on cardiac response to environmental stimuli and subsequent response selection (e.g. maintenance of resting homeostasis, mobilization of defensive response, task performance, tonic immobilization, and/or affiliation) will be explored. Reference will be made to how these processes conjoin with proposed polyvagal theory. Cardiac adjustments to environmental stimuli affect the internal physiological state of the organism as well as the quality of information processing that the individual can perform during the stimulus appraisal stage of the orienting response. Bradyrdia is adaptive in early stages of orientation to novel or potential threat, while greater HRV power serves to facilitate self-regulation, stimulus information processing and appraisal, and appropriate response selection. This issue is devoted to current research findings on how normal patterns of cardiac autonomic regulation of HRV are disrupted in PTSD, impairing sustained attention to the environment and increasing the rate of inappropriate responding to stimuli. Origins of our current state of understanding in the 'intake-rejection' hypothesis will be considered, and how the intake-rejection hypothesis has morphed into present-day Optimal Performance practice. Additionally, empirical data where available will be presented on how dysregulation of the normal pattern of cardiac autonomic regulation by PTSD impairs sustained attention to the environment, and increases the rate of inappropriate responding to stimuli through disinhibition, poor impulse control, emotional withdrawal, over-arousal, and attentional bias. Current research findings are sought that address in controlled, experimental and clinical trials the restorative effects of HRV biofeedback on HRV power, and how increases in HRV power relate to improved attention / immediate memory and self-regulation of affect using outcome measures of cognition, symptoms of PTSD and depression, stress perception, and level of adaptive function.